A Review on the Air Flow Behaviour in the Intake Pipe - Lim*, J.W.; N., Narendran; Chai, C.E.; M.I.N, Ma'arof (IOP Publishing, 2020)
The air flow behaviour plays an important role to provide the better ram air effect inside the intake manifold for combustion. The aim of this study is to review various research paper on air flow in the intake manifold. The study is mainly focussed on the geometrical influence in the air flow behaviour in the intake pipe. Most of the studies emphasized on the computational fluid dynamics (CFD) software which is utilized as tool to investigate the air flow behaviour in the pipe. The important variables that taken into consideration are the shape of pipe inlet, intake pipe diameter, and bending angle of the intake pipe. By conducting the review on the papers, the possible alternatives could be obtained to overcome the air restrictions in the intake pipe and increase the performance of the engine.